Different incubation patterns affect selective antimicrobial properties of the egg interior: experimental evidence from eggs of precocial and altricial birds - Svobodová, Jana; Šmídová, Lucie; Javůrková, Veronika Gvoždíková (The Journal of experimental biology, 2019)
Avian eggs contend with omnipresent microorganisms entering the egg interior, where they affect embryo viability and hatchling phenotype. The incubation behaviour and deposition of egg white antimicrobial proteins (AMPs) vary highly across the avian altricial-precocial spectrum. Experimental evidence of how these alterations in avian reproductive strategies affect the antimicrobial properties of the precocial and altricial egg interior is lacking, however. Here, we tested the egg white antimicrobial activity in eggs of two representative model species, from each end of the avian altricial-precocial spectrum, against potentially pathogenic and beneficial probiotic microorganisms. Eggs were experimentally treated to mimic un-incubated eggs in the nest, partial incubation during the egg-laying period, the onset of full incubation and the increased deposition of two main egg white AMPs, lysozyme and ovotransferrin. We moreover assessed to what extent egg antimicrobial components, egg white pH and AMP concentrations varied as a result of different incubation patterns. Fully incubated precocial and altricial eggs decreased their antimicrobial activity against a potentially pathogenic microorganism, whereas partial incubation significantly enhanced the persistence of a beneficial probiotic microorganism in precocial eggs. These effects were most probably conditioned by temperature-dependent alterations in egg white pH and AMP concentrations. While lysozyme concentration and pH decreased in fully incubated precocial but not altricial eggs, egg white ovotransferrin increased along with the intensity of incubation in both precocial and altricial eggs. This study is the first to experimentally demonstrate that different incubation patterns may have selective antimicrobial potential mediated by species-specific effects on antimicrobial components in the egg white.
Keywords: Bacillus subtilis; Ovum; ovum; Embryo viability; vaječný bílek; ptačí proteiny; Reproduction; Albumen; Avian Proteins; rozmnožování; Anti-Infective Agents; ovotransferin; Incubation onset; Antimicrobials; Egg White; Animals; Muramidase; Columbidae; zvířata; Conalbumin; Trans-shell infection; Micrococcus luteus; antiinfekční látky; muramidasa; Coturnix